2017
DOI: 10.1051/matecconf/20178702030
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cutting Edge Temperature and Cutting Force of End Mill Tool in High Speed Machining

Abstract: Abstract.A wear of cutting tools during machining process is unavoidable due to the presence of frictional forces during removing process of unwanted material of workpiece. It is unavoidable but can be controlled at slower rate if the cutting speed is fixed at certain point in order to achieve optimum cutting conditions. The wear of cutting tools is closely related with the thermal deformations that occurred between the frictional contact point of cutting edge of cutting tool and workpiece. This research paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The higher temperature is reported at higher cutting speeds (182 and 140 m/min) whereas; the variation of temperature due to varying feed is uneven. The depth of cut influencing significantly to the cutting temperature as temperature is increasing with improving the depth of cut because of the higher plastic deformation at the primary and secondary deformation region [22]. ANOVA (Table 4) ensured that the cutting speed (76.8 % contribution) is highly significant for temperature (T) succeeded by the depth of cut (18.8 % contribution) while the feed is irrelevant [23].…”
Section: Discussion On Aspects Of Chip-tool Interface Temperaturementioning
confidence: 99%
“…The higher temperature is reported at higher cutting speeds (182 and 140 m/min) whereas; the variation of temperature due to varying feed is uneven. The depth of cut influencing significantly to the cutting temperature as temperature is increasing with improving the depth of cut because of the higher plastic deformation at the primary and secondary deformation region [22]. ANOVA (Table 4) ensured that the cutting speed (76.8 % contribution) is highly significant for temperature (T) succeeded by the depth of cut (18.8 % contribution) while the feed is irrelevant [23].…”
Section: Discussion On Aspects Of Chip-tool Interface Temperaturementioning
confidence: 99%
“…A schematic illustration of the experimental setup was shown in Figure 1 and based on previous research [6][7][20][21]. A single indexable end milling cutter was used and optical fiber was positioned at an angle of 180 o from the initial contact point of end mill tool on the workpiece.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Ueda, Hosokawa, Oda and Yamada (2001) [6] also found that increasing cutting speed will reduce finished surface temperature, but increasing tool-chip contact temperature. Furthermore, Ueda et al (2001) [6] and Kiprawi, Yassin, Syed Shazali, Islam, & Mohd Said (2017) [7] studied the effects of cutting speed and depth of cut on cutting tool temperature of cemented carbide insert. They concluded that the increasing cutting speed and depth of cut will increase the cutting temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations